Maqasid As-Sharia Hifz Al-Bi'ah in Responding to the Policy of the Cement Factory In Pati - Muhammad Labib Salim (The Institute of Research and Service Community IPMAFA Pati, 2021)
This article discusses the policy on the plan to build a cement factory in Pati Regency which triggered a long conflict between PT Sahabat Mulia Saktin as the corporation, the Pati Regency Government, and the society around the Kendeng Mountains in Pati, which was analyzed interdisciplinary based on the approach of public policy reasoning and maqashid sharia hifzu al-bi' ah. The academic problem in this study is that, there are differences basic paradigms behind the actions of each of these parties. This research is a literature study with a qualitative-descriptive method. The data are taken from previous research publications, online news as well as trusted online sites. Meanwhile, in the analysis process the method of Miles and Huberman is use maximally. The results of the analysis process concluded that the genealogy of the public policy formulation process was carried out starting from the agenda setting (2010), legitimacy and formalization (2010 – 2011), implementation (2011 – 2014), and, policy evaluation (2015-present). By using maqashid sharia hifzu al-bi'ah reasoning, it is concluded objectively and neutrally that policies tend to lead to claims of mafsadah (badness). A recommendation worth considering is the initiation of the ijtihad jama'i forum by presenting expert sources in various relevant fields, far from political interests and subjectivity, so that alternative benefits are formulated for the phenomenon of policy and conflict in cement factories.